Investigation of red blood cell and platelet indices in adult dogs suffered from myxomatous mitral valve disease with and without pulmonary hypertension - Tangmahakul, Nattawan; Orton, E. Christopher; Surachetpong, Sirilak Disatian (Frontiers in Veterinary Science, 2023)
Pulmonary hypertension (PH) is a common complication of cardiopulmonary disease. In dogs, PH commonly occurs secondary to myxomatous mitral valve disease (MMVD). Red blood cell and platelet indices including mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), mean corpuscular hemoglobin concentration (MCHC), red cell distribution width (RDW), mean platelet volume (MPV) and platelet distribution width (PDW), have previously been found to be indicators for predicting and prognosing PH in humans. Therefore, this study aimed to investigate whether these indices are associated with MMVD and/or PH in dogs. Two hundred and forty-six dogs were retrospectively recruited for the study and classified into 4 groups: normal (n=49), MMVD (n=102), PH (n=17), MMVD+PH (n=78). A sub-analysis was performed in dogs with MMVD without evidence of PH according to stage B1 (n=20), stage B2 (n=15), stage C (n=67). The data are expressed as median (interquartile range). No significant differences (p<0.05) were found in MCV,